Economic growth in the very long-run - Oded Galor (Brown University, Department of Economics, 2006)
The evolution of economies during the major portion of human history was marked by Malthusian Stagnation. The transition from an epoch of stagnation to a state of sustained economic growth has shaped the contemporary world economy and has led to the Great Divergence in income per capita across the globe in the past two centuries. This entry examines the process of development over the course of human history and its implications from comparative development in light of recent advances in Unified Growth Theory.
Keywords: O11; O14; O33; O40; J11; J13; 330; Wirtschaftswachstum